PENERAPAN MULTIMEDIA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA ISLAM NUSANTARA MALANG - Agung Maulana; Muhammad Fahmi Hidayatullah; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The development of learning technology continues to shift little by little over time causing the use of multimedia in learning to become a common thing. The research entitled the application of multimedia in learning Islamic religious education at SMA Islam Nusantara Malang has the aim of describing the planning, and control of multimedia application in learning Islamic religious education at SMA Islam Nusantara Malang. The method used in this research is qualitative research with the type of case study research. Based on the results of the analysis, it can be concluded that: (1) The learning planning process using multimedia in Islamic religious education learning at SMA Islam Nusantara Malang is planning for multimedia learning in a computer laboratory which is carried out by preparing multimedia-based learning facilities and infrastructure, such as computers, LCDs, projectors, sound system and internet network. (2) The process of controlling the application of multimedia in learning Islamic religious education at SMA Islam Nusantara Malang is the process of implementing learning in the computer laboratory, namely: explaining the material, seeking additional information via the internet, discussing, concluding the ongoing learning.Â